Modeling and simulation of turbulent non-reacting and reacting spray flows - Ge, Hai-Wen; Gutheil, Eva (Reactive flows, diffusion and transport, 2007)
The scope is the modeling and simulation of turbulent spray flames where the emphasis is the modeling of the interaction of the vaporization and the turbulent flow field. In particular, the mixing process as well as the interaction of the turbulent flame with the vaporization are studied. These processes are least understood when it comes to the simulation of dilute spray flames.